Role of the lncRNA–mRNA network in atherosclerosis using ox-low-density lipoprotein-induced macrophage-derived foam cells. (11th September 2020) - Zhang, Caijuan; Zhang, Xin; Gong, Yiting; Li, Tong; Yang, Le; Xu, Wenjuan; Dong, Ling
Abstract : Atherosclerosis (AS) is the leading cause of coronary heart disease, cerebral infarction, peripheral vascular disease, we explored the roles of key genes in atherosclerosis via an ox-low-density lipoprotein induced macrophage-derived foam cell model. Abstract : Atherosclerosis (AS) is the leading cause of coronary heart disease, cerebral infarction, peripheral vascular disease, and other cardiovascular diseases, making it a major risk factor for high morbidity and mortality. Although long non-coding RNAs (lncRNAs) have been reported to play a role in AS, the specific effects of lncRNAs on AS remain largely unknown. Thus the purpose of this study was to explore the roles of mRNAs and lncRNAs in atherosclerosis via an ox-low-density lipoprotein induced macrophage-derived foam cell model. Microarray analysis identified a total of 50 688 mRNAs and 1514 lncRNAs, including 51 lncRNAs and 1730 mRNAs that were significantly dysregulated in the model group ( p -adjust < 0.05 and |log 2FC| > 2). The results of gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses demonstrated that the dysregulated genes were associated with cell proliferation, cell apoptosis, and inflammatory responses. An lncRNA–mRNA co-expression network was created to further analyze the key regulatory genes. The lncRNAs Brip1os, Gm16586, AU020206, 9430034N14Rik, 2510016D11Rik, LNC_000709, Gm15472, Gm20703, and Dubr were identified as potential biomarkers in macrophage-derived foam cells. Based on 9 lncRNAs and 13 mRNAs, key genes influencing the degree of cell proliferation and cell apoptosis and the subsequent development of AS were identified. Q-PCR verified the key dysregulated genes. Thus, our results suggest potential therapeutic targets for AS and provide avenues for further research on AS pathogenesis.